Nuclear Level Density Parameters of Pb203-209 and Bi206-210 Deformed Target Isotopes Used on Accelerator-Driven Systems in Collective Excitation Modes - Şeref Okuducu; Nisa N. Aktı; Sabahattin Akbaş; M. Orhan Kansu (Science and Technology of Nuclear Installations)
The nuclear level density parameters of some deformed isotopes of target nuclei (Pb, Bi) used on the accelerator-driven subcritical systems (ADSs) have been calculated taking into consideration different collective excitation modes of observed nuclear spectra near the neutron binding energy. The method used in the present work assumes equidistant spacing of the collective coupled state bands of the considered isotopes. The present calculated results for different collective excitation bands have been compared with the compiled values from the literature for s-wave neutron resonance data, and good agreement was found.